Involvement of a caleosin in lipid storage, spore dispersal, and virulence in the entomopathogenic filamentous fungus, Beauveria bassiana. (19th August 2015) - Fan, Yanhua; Ortiz‐Urquiza, Almudena; Garrett, Timothy; Pei, Yan; Keyhani, Nemat O.
Summary: Eukaryotic cells store lipids in membrane‐encased droplets. The entomopathogenic fungus, B eauveria bassiana, initiates infection via attachment of its spores to the epicuticle or waxy layer of target insects, degrading and assimilating host surface hydrocarbons, carbohydrates and proteins. Caleosins are components of the proteinaceous coat of lipid droplets and a single B . bassiana caleosin homologue, B bcal1, was identified and characterized. The BbCal1 sequence contained an EF‐hand Ca 2+ binding domain and potential hydrophobic stretches similar to those found in plant caleosins, along with a proline knot motif defined by only two proline residues. Targeted gene inactivation of B bcal1 did not appear to affect spore germination, growth on lipid substrates or stress response, but changes in lipid, vacuole and endoplasmic reticulum/multilamellar vesicle‐like structures, and altered cellular lipid profiles were seen in conidia grown on a variety of substrates including potato dextrose agar, olive oil, glyceride trioleate, oleic acid and the alkane, C16 . The Δ B bcal1 mutant produced more compact assemblages of conidia, displayed a reduced and delayed spore dispersal phenotype, and showed decreased virulence in insect bioassays using the greater wax moth, G alleria mellonella . Our data indicate novel functions for caleosins in fungal virulence, spore development and the trafficking and/or turnover of lipid‐related structures.